2023
DOI: 10.1186/s42408-022-00163-2
|View full text |Cite
|
Sign up to set email alerts
|

Fuel treatment effectiveness at the landscape scale: a systematic review of simulation studies comparing treatment scenarios in North America

Abstract: Background The risk of destructive wildfire on fire-prone landscapes with excessive fuel buildup has prompted the use of fuel reduction treatments to protect valued resources from wildfire damage. The question of how to maximize the effectiveness of fuel reduction treatments at landscape scales is important because treating an entire landscape may be undesirable or unfeasible. We reviewed 86 simulation studies that examined landscape-scale fuel reduction treatment effectiveness for landscapes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 133 publications
(334 reference statements)
0
8
0
Order By: Relevance
“…There is substantial evidence that fuel reduction can be effective at mitigating wildfire risk 24,29 , but studies to date tend to be on small scales, for particular circumstances (e.g., refs. [30][31][32][33][34][35] ), and it is unclear if they generalize to broad spatial scales, if they are consistent for extreme and non-extreme fire weather conditions 36 and to what degree the effects of fuel reduction could counteract projected climate warming 37 .…”
Section: Mainmentioning
confidence: 99%
“…There is substantial evidence that fuel reduction can be effective at mitigating wildfire risk 24,29 , but studies to date tend to be on small scales, for particular circumstances (e.g., refs. [30][31][32][33][34][35] ), and it is unclear if they generalize to broad spatial scales, if they are consistent for extreme and non-extreme fire weather conditions 36 and to what degree the effects of fuel reduction could counteract projected climate warming 37 .…”
Section: Mainmentioning
confidence: 99%
“…However, the informational basis regarding fuel treatment effectiveness is mixed. Empirical analyses have found that treatments can be effective at reducing fire intensity and severity within treated areas, but evidence of their effectiveness at landscape scales is limited ( Fernandes, 2015 ; Kalies and Kent, 2016 ; McKinney et al, 2022 ; Ott et al, 2023 ; Urza et al, 2023 ). This gap is critical as many existing or proposed treatments are not directly located in the WUI but rather in proximal wildlands, based on the premise that treatments will interrupt fire spread and reduce WUI exposure.…”
Section: Introductionmentioning
confidence: 99%
“…This gap is critical as many existing or proposed treatments are not directly located in the WUI but rather in proximal wildlands, based on the premise that treatments will interrupt fire spread and reduce WUI exposure. Simulation modeling is widely used to fill that gap, showing how treatments can affect metrics such as landscape burn probability ( Ott et al, 2023 ). However, in almost all cases, simulation modeling is used to evaluate hypothetical future treatments (e.g., Benali et al, 2021 ; Alcasena et al, 2022 ), with few examples that analyze how prior treatment interactions with wildfires may have altered landscape outcomes (e.g., Cheney, 2010 ; Cochrane et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prescribed fires are controlled applications of fire used to reduce woody and herbaceous fuels and suppress the potential for wildfires with far greater hazard potential. Prescribed fire is now widely used as a management tool to achieve the social, economic, and ecological benefits of fire while reducing the risks associated with uncontrolled wildfires [12][13][14][15]. Wildfires that burn in areas where prescribed fire has been used to suppress fuels can have lower intensities and extents, cause less damage, and be easier to control [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We collaborated with regional fire management experts to develop a BN model that integrated spatial data to estimate wildfire risk for forests across the Southeastern United States and evaluate the role that prescribed fire can play in managing risk. The Southeastern US serves as a model region for the widespread use of prescribed fire to manage wildfire risks and forest ecological conditions [14,33]. Enhanced investments in risk management, including active management to reduce fuels in forest landscapes, will be required to confront growing risks.…”
Section: Introductionmentioning
confidence: 99%